Cine drive-in as a possibility for artistic leisure during the COVID-19 pandemic period (Research, Society and Development, 2021)
Leisure has as its basic principles the availability of time and the subject's freedom to choose to experience something. Therefore, freedom of choice (attitude) becomes a fundamental factor. However, since March 2020, the Brazilian population faces a new barrier, SARS-COV2, a highly infectious virus, responsible for the dissemination of COVID-19. Due to the lack of vaccine, social distance, facial protection with a mask and hand hygiene with alcohol were (or should have been) the main biosecurity measures, which limited several daily activities to the residential context. By recognizing leisure as an important element to life and a social right, the Federal University of Mato Grosso do Sul (UFMS) formalized partnerships and created conditions to offer experiences of artistic interest in leisure through the projection of movies in the drive in format, from June to December 2020, at the AutoCine, specific leisure equipment that since 1989 has been inoperative. The present manuscript, characterized as described and experience report, aims to present and describe the project “Autocine UFMS: reliving stories, giving new meaning to leisure spaces and experiences in times of pandemic”.